Resolving blood group discrepancy in patients of tertiary care centre in Odisha, India - Mishra, Debasish; Parida, Pankaj; Mahapatra, Smita; Sahoo, Binay Bhusan (International Journal of Research in Medical Sciences, 2018)
Background: Blood grouping consists of both forward grouping; reverse grouping and both procedures should agree with each other.A blood group discrepancy exists when results of red cell testing do not agree with serum testing, usually due to unexpected negative or positive results in either forward or reverse typing. ABO and Rh blood group discrepancy is associated with incompatible transfusion reaction.Blood group discrepancy should be resolved before transfusion and blood group to be properly labeled to prevent transfusion reaction. Methods: A prospective study was carried in SCB blood bank which is under the Department of Transfusion Medicine, SCB Medical College and Hospital, Cuttack, Odisha from January 2015 to October-2016. Total 25,559 blood samples of patients were included in the study and hemolysed samples excluded. The ABO and Rh D typing was done by tube technique using monoclonal IgM (Tulip Diagnostic P Ltd.) Anti-A, Anti-B, Anti-D and pooled A, B and O cell. Results: A total of 25,559 blood group testing were done where we found 57 blood group discrepancies with overall frequency was 0.22%. Out of 57 discrepancies we were found 20 (35.09%) cases of technical error and 37 (64.91%) cases of sample related error. Among these sample related problems, we found weak/missing antibody, weak antigen expression, rouleaux, cold autoantibodies, cold alloantibodies, Bombay phenotype with the frequency of 13.51%, 2.70%, 2.70%, 54.06%, 8.11%, 18.92% respectively. Conclusions: Mistyping either a donor or a recipient can lead to transfusion with ABO-incompatible blood, which can result in severe hemolysis and may even result in the death of the recipient. Any discrepancy between forward and reverse blood grouping methods should be resolved before transfusion of blood components.